2022
DOI: 10.3390/medicina58091268
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Questionnaire-Based Survey on Blood-Borne Infection Control among Romanian Dental Students

Abstract: Background and Objectives: According to the CDC estimates, 5.6 million healthcare workers worldwide are exposed to the risk of occupationally contracting blood-borne pathogens, including human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), and others. The aim of the present study was to assess the knowledge level on blood-borne infection control (IC) among Romanian undergraduate dental students. Materials and Methods: A cross-sectional, questionnaire-based survey with 21 items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…Among these, most (55.0%) did not investigate the source patient's bloodborne virus status and 80.5% did not consult an infectious disease specialist for guidance related to post-exposure prophylaxis (PEP). This is in line with the above-mentioned questionnaire-based study from Ias , i, which showed that only half (50.2%) of the students were aware of the key moments when testing for BBV should be performed after an accidental exposure [17]. In our current study, even among the few respondents who did consult an infectious disease practitioner, only a small fraction presented for the consult on the first day following exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among these, most (55.0%) did not investigate the source patient's bloodborne virus status and 80.5% did not consult an infectious disease specialist for guidance related to post-exposure prophylaxis (PEP). This is in line with the above-mentioned questionnaire-based study from Ias , i, which showed that only half (50.2%) of the students were aware of the key moments when testing for BBV should be performed after an accidental exposure [17]. In our current study, even among the few respondents who did consult an infectious disease practitioner, only a small fraction presented for the consult on the first day following exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing year of study was significantly correlated with better knowledge of VPDs. This effect was also seen in a different questionnaire-based study from Ias , i, Romania, where higher year students more accurately recognized HBV as a VPD [17]. However, an important finding of our current study is that increasing year of study was not correlated with self-perceived risk and neither with the willingness to treat patients with chronic viral infections, which highlights an important unmet need and suggests that the current university curricula should be revised to include more targeted information regarding the actual dimension of the risk of transmission of HBV, HCV, and HIV in dental practice.…”
Section: Discussionmentioning
confidence: 58%